Study on clinicopathological characteristics of pituitary adenomas according to types of transcription factors - 엄소영 (The Graduate School, Ajou University, 2024)
A tumor arising from the pituitary gland, located in the lower part of the central brain, is called a pituitary adenoma. Pituitary adenomas are generally benign tumors, and their clinical and pathological classification has traditionally been based on factors such as tumor size, the presence of clinical symptoms due to hormone secretion, and the type of hormone produced by the adenoma. However, recent World Health Organization (WHO) tumor classifications have introduced new criteria based on the expression patterns of transcription factors and cell origin. This study aimed to analyze the clinical characteristics of patients diagnosed with pituitary adenoma at Ajou University Hospital and to reclassify them based on the new transcription factor-based classification criteria proposed by the WHO. A total of 555 specimens from patients diagnosed with pituitary adenoma were retrospectively reviewed, and among them, tissue microarrays (TMA) were constructed for 362 patients. Recurrence occurred in 22 patients, and hormone-induced clinical symptoms appeared in the late recurrence group. Upon applying the new classification criteria, gonadotroph tumors were the most frequently observed subtype, with 180 cases. Rare tumors such as thyrotroph tumor, acidophil stem cell tumor and Crooke cell tumor were not observed. Patients showing immune negative reactions for all hormones and transcription factors were classified as null cell tumors, with a total of 18 cases. The results of this study provide insights into the clinical and pathological characteristics of pituitary adenomas in Koreans.
학위논문(석사)--의생명과학과,2024. 2
Keywords: neuroendocrine tumors; pituitary adenoma; pituitary neoplasm; transcription factors